2022
DOI: 10.1002/cctc.202101736
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Phosphino‐naphtholate Nickel Complexes and Their Catalysis of Copolymerization with Polar Monomers

Abstract: Coordination-insertion copolymerization of ethylene with polar monomers can directly provide value-added functionalized polyolefins. Studies on the reactivity of catalysts toward polar monomers can help understand the copolymerization process and then tune the polymerization strategically. In this contribution, the reactivity picture of 2-diphenylphosphonyl-8-phenylnaphthol nickel complex toward fundamental polar monomers was explored by stoichiometric reactions. The insertion rates are in the order of methyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…27 nm indicates the oxidation to the graphitic structure confirming the formation of GO from graphite. Other peaks obtained at 28.08 and at 46 are due to the graphitic disorder after the oxidation process, and it arises due to the (002) graphitic plane.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…27 nm indicates the oxidation to the graphitic structure confirming the formation of GO from graphite. Other peaks obtained at 28.08 and at 46 are due to the graphitic disorder after the oxidation process, and it arises due to the (002) graphitic plane.…”
mentioning
confidence: 90%
“…The combination of NVP and MMA in copolymerization can be accomplished through different methods, including solution polymerization, emulsion polymerization, and miniemulsion polymerization, as indicated by various sources. 26,27 The selection of the polymerization method and specific reaction conditions significantly impacts the copolymer's composition, molecular weight, and overall properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this catalytic system, they further reported a coherent study of insertion rate, insertion mode and copolymerization reaction on various fundamental polar monomers, affording directions to rationally design catalysts. The acrylic derivatives displayed higher reactivity than non-acrylic polar monomers in the order of MA > n-butyl acrylate (BA) > N,N-dimethylacrylamide (DMAA) > MMA > vinyl triethoxysilane (VTEOS) > N-vinyl-pyrrolidinone (NVP), and the electron-deficient acrylic derivatives prefer 2,1-fashion while the electron-rich vinyl polar monomers favor 1,2-insertion [110]. Instead of tuning steric bulk from the "P"-side, Theodor Agapie et al reported two neutral Ni(II) catalysts 19 (Figure 16) that displayed steric bulk on the "O"-side of the phosphino-phenoxide ligand as a rotationally flexible phosphine substituent (POP ligand 19a) and a rigid aryl derivative (PONap ligand, 19b) [111].…”
Section: Phosphine-phenolate Nickel Catalystsmentioning
confidence: 99%
“…This has been the motivation for the significant growth in this area in recent years. As a result, several substantial improvements have been made in catalyst stability and copolymerization activity in the presence of a variety of polar functional groups. , …”
Section: Introductionmentioning
confidence: 99%